2014
DOI: 10.1177/2050313x14532250
|View full text |Cite
|
Sign up to set email alerts
|

Fatal case of cephalexin-induced toxic epidermal necrolysis

Abstract: Purpose:To describe a case of toxic epidermal necrolysis likely caused by cephalexin with a review of the literature.Case:An 80-year-old male with a known allergy to cephalosporins, residing at a long-term acute care hospital, received cephalexin for a urinary tract infection. And 1 day after starting therapy, the patient developed an extensive erythematous rash accompanied by skin sloughing; 4 days after receiving cephalexin, the patient was directly admitted to the burn intensive care unit and was diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In our patient, acute kidney injury may be responsible for her rapid decline and is an independent risk factor for increased mortality in TEN [7]. It is well documented in the literature that antimicrobials such as cephalosporins and fluoroquinolones can induce SJS and TEN [8][9][10][11], which our patient was receiving. Although high-risk agents were stopped immediately upon her diagnosis, SJS/TEN can occur a few days after the offending drug has been withdrawn in the case of long-half-life drugs.…”
Section: Discussionmentioning
confidence: 57%
“…In our patient, acute kidney injury may be responsible for her rapid decline and is an independent risk factor for increased mortality in TEN [7]. It is well documented in the literature that antimicrobials such as cephalosporins and fluoroquinolones can induce SJS and TEN [8][9][10][11], which our patient was receiving. Although high-risk agents were stopped immediately upon her diagnosis, SJS/TEN can occur a few days after the offending drug has been withdrawn in the case of long-half-life drugs.…”
Section: Discussionmentioning
confidence: 57%
“…Multiple studies revealed that cephalosporins are the culprit in inducing TEN. 6,18,19 The presumption, in this case, was that the patient developed TEN due to the consumption of cefadroxil for the complaints of fever, throat and abdominal pain. The likelihood of the adverse reaction being attributed to cefadroxil was evaluated using the Naranjo probability scale.…”
Section: Discussionmentioning
confidence: 93%